2007
DOI: 10.2220/biomedres.28.323
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium chloride suppresses styrene-induced cytochrome P450s expression in rat liver

Abstract: To assess the effect of gadolinium (Gd) on the expression of several forms of cytochrome P450 (P450s) and antioxidant enzymes, we treated rats with gadolinium chloride (25 mg as Gd/kg body weight) 4 h after styrene (a multiple P450 inducer) treatment (600 mg/kg). Gd treatment significantly suppressed styrene-inducible cytochrome P4502B1 (CYP2B1), CYP2B2, CYP2E1, and CYP3A2 mRNA expressions to 48.6%, 69.8%, 61.1%, and 38.5%, accompanying with the reduction of proteins expression to 1.42%, 31.2%, 21.1% and 21.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The effect of ST on experimental animals was reported by several investigators (7,15,22,23). Hirasawa et al (2007) reported that serum AST and ALT activities were significantly increased in rats treated with ST (22). Elevation of ALT and AST was noted in workers exposed to ST (24,25).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The effect of ST on experimental animals was reported by several investigators (7,15,22,23). Hirasawa et al (2007) reported that serum AST and ALT activities were significantly increased in rats treated with ST (22). Elevation of ALT and AST was noted in workers exposed to ST (24,25).…”
Section: Discussionmentioning
confidence: 91%
“…We found that ST induced dose-dependent elevations of ALT, AST, and alkaline phophatase in rat liver. The effect of ST on experimental animals was reported by several investigators (7,15,22,23). Hirasawa et al (2007) reported that serum AST and ALT activities were significantly increased in rats treated with ST (22).…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, there are few reports showing protective effects of GdCl 3 treatments in isolated hepatocytes. It was shown that Gd 3+ can reduce the levels of cytochrome P450 in hepatocytes [ 52 ], which in turn can reduce oxidative damage. Oxidative damage is an important feature in NPC; therefore, Gd 3+ can contribute to the beneficial effects observed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Harstad and Klaassen suggest that GdCl 3 may increase hepatic metallothionein, and thus protect the liver from cadmium-induced liver injury [28]. Moreover, Hirasawa et al demonstrate that GdCl 3 can penetrate into hepatocytes and protect isolated hepatocytes in vitro by affecting cytochrome P450 [29]. Interestingly, GdCl 3 has been shown to affect the function of gap junction hemi-channels in Xenopus laevis (African Claw Frog) oocytes as a chloride-channel blocker [30].…”
Section: Introductionmentioning
confidence: 99%